Cointegration and the demand for energy in Fiji. (10th May 2011) - Kumar, Saten
This paper applies alternative time series techniques such as general to specific (GETS) and Johansen maximum likelihood (JML) to estimate the long-run income and price elasticities of demand for energy for Fiji. We also test for the causal relationship between energy consumption, GDP and energy prices using the Granger causality tests. Our results imply that there is a uni-directional causality running from GDP to energy consumption.